Foot and ankle service adaptation in response to COVID-19 and beyond. (June 2020) - Feeley, I.; McAleese, T.; Clesham, K.; Moloney, D.; Crozier-Shaw, G.; Hughes, A.; Bayer, T.
Abstract: The disruption to healthcare provision as a result of the COVID-19 pandemic has compelled us to streamline healthcare delivery. This has given us an opportunity to implement healthcare technology, reform inter-disciplinary collaboration and ultimately enhance patient care. We discuss some of the advances made by the foot and ankle department at our hospital. These innovations have broad applicability and will hopefully ignite discussion amoung a number of healthcare teams about improving the future care of their patients.